(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As an inclusive policy, the Karnataka government has been working hard to support and foster the self-help movement. This is made abundantly visible by the enormous growth in the number of Self help Groups in the State; as of right now, 6, 88,253 Self-help Groups-or 27% of all Self-help Groups nationwide-are limited to Karnataka. Self-help groups are expected to contribute to the socioeconomic advancement of rural women generally and the social inclusion of Scheduled Caste women, who are among the most marginalised, specifically. In Karnataka, Self-help Groups have been a surprise for women living in rural areas, bringing about social and economic empowerment as well as a silent revolution. The World Bank expressed its admiration for the outstanding achievements of women’s self-help groups in Karnataka and suggested that other Indian states and foreign nations could adopt the same model. Celebrities that visited the State to engage with the womenSelf-Help Groups, including Bill Clinton, George W. Bush, Bill Gates, and Sonia Gandhi, were impressed with their performance and accomplishments. The Scheduled Caste Women experienced gender-specific disadvantages in addition to caste-related ones, which led to their total and thorough exclusion. They were discriminated against among the discriminating, and underprivileged among the underprivileged.